Frameworks for IT management : a pocket guide - Rozemeijer, Eric; Van Bon, Jan.; Verheijen, Tieneke; IT Service Management Forum (Zaltbommel, The Netherlands : Van Haren, 2007)
Includes framework models such as: ITIL, ISO 20000, ISO 27000, ISO9000, PRINCE2', IPMA Competence Baseline, PMBoK, CobiT, MSP, M_o_R, ISPL, ITS-CMM, ASL, BiSL, Six Sigma, TickIT, PrimaVera, eTOM, TQM, AS8015, eSCM, and Balanced ScoreCard.
oif 02/06/14
Loan
Keywords: Information technology -- Management; Information technology -- Quality control -- Standards